KONSEP MUSIK PAKELIRAN PILIHAN GARAP K1 PURBO ASMORO - Sarno Sarno (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2003)
The Concept of Wayang Accompaniment of PurboÂ Asmoro The wayang pe,formance of Pu,bo AsmoroÂ isÂ relatedÂ Itâ€™Â condensed shadow puppetperformance (pake/i,~n padat). This can be seen fivm: the dear messages, the efficient treatment of the stofy, and the omission of unnecessary idioms. For thatreason, he does not feel necessary to use the â€œhugeâ€ ensemble of campursari (the hybrid style between game/an and popular music). The concept of musicalaccompaniment makes it possible to use alternate source and be effective in using the music.